2020
DOI: 10.3126/njb.v8i3.30080
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram of Escherichia coli and Staphylococcus aureus isolated from milk sold in Kathmandu district

Abstract: The emergence of antibiotic resistance in microorganisms and the presence of such isolates in milk pose a great risk to public health. Therefore, this study aims to determine the antibiotic susceptibility pattern of Escherichia coli and Staphylococcus aureus isolated from milk and assess the microbial quality of milk. For this, a total of 70 milk samples were collected and the total bacterial count (TBC) was determined. E. coli and S. aureus were isolated using their respective selective media while antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 15 publications
5
9
4
Order By: Relevance
“…The percentage of MDR isolates of E. coli observed in our finding was much higher than that detected in previous studies of Mekelle, Ethiopia (28.24%), 2 Indonesia (9.1%) 38 and Nepal (28%). 39 According to our results, the observed patterns reflect the use of these antimicrobials in the study area, and it shows that E. coli has been exposed to these drugs. Another possible reason for the observed pattern is the availability and price of these drugs.…”
Section: Resultssupporting
confidence: 55%
“…The percentage of MDR isolates of E. coli observed in our finding was much higher than that detected in previous studies of Mekelle, Ethiopia (28.24%), 2 Indonesia (9.1%) 38 and Nepal (28%). 39 According to our results, the observed patterns reflect the use of these antimicrobials in the study area, and it shows that E. coli has been exposed to these drugs. Another possible reason for the observed pattern is the availability and price of these drugs.…”
Section: Resultssupporting
confidence: 55%
“…If the contamination in paneer is from milk samples then the high percent of MDR may be due to high and unchecked usage of antibiotics in cattle for breeding and treatment like the use of beta-lactam antibiotics to treat mastitis in cattle. Evidently, higher proportion of MDR in milk has been reported by Rai et al (2020) in Kathmandu. Further, if the contamination is due to the environment or contact surface, then it may be due to a gene transfer or mutation in the bacteria.…”
Section: Antibiotic Susceptibility Patternmentioning
confidence: 94%
“…According to the WHO, at least 700,000 people die each year due to drug-resistant diseases, which could escalate to 10 million deaths per year by 2050 [7]. Such an escalation of AMR is a serious concern, specifically the resistance towards the available drugs [3][4][5]8], which may limit the treatment options. Several studies around the world have reported the presence of AMR coliforms such as E. coli in milk samples [1,4,5,[8][9][10], and the results of those studies have clearly shown the rising trend of AMR among milk pathogens [4-5, 8, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Such an escalation of AMR is a serious concern, specifically the resistance towards the available drugs [3][4][5]8], which may limit the treatment options. Several studies around the world have reported the presence of AMR coliforms such as E. coli in milk samples [1,4,5,[8][9][10], and the results of those studies have clearly shown the rising trend of AMR among milk pathogens [4-5, 8, 10]. In particular, the most common antibiotic resistance conferred by these coliforms is toward the βlactam class of antibiotic [4][5]8].…”
Section: Introductionmentioning
confidence: 99%